Molecular mimicry of host sialylated glycans allows a bacterial pathogen to engage neutrophil Siglec-9 and dampen the innate immune response - Carlin, Aaron F. (American Society of Hematology, 2009)
Human neutrophil Siglec-9 is a lectin that recognizes sialic acids (Sias) via an amino-terminal V-set Ig domain and possesses tyrosine-based inhibitory motifs in its cytoplasmic tail. We hypothesized that Siglec-9 recognizes host Sias as “self,” including in cis interactions with Sias on the neutrophil's own surface, thereby dampening unwanted neutrophil reactivity. Here we show that neutrophils presented with immobilized multimerized Siaα2-3Galβ1-4GlcNAc units engage them in trans via Siglec-9. The sialylated capsular polysaccharide of group B Streptococcus (GBS) also presents terminal Siaα2-3Galβ1-4GlcNAc units, and similarly engages neutrophil Siglec-9, dampening neutrophil responses in a Sia- and Siglec-9–dependent manner. Reduction in the neutrophil oxidative burst, diminished formation of neutrophil extracellular DNA traps, and increased bacterial survival are also facilitated by GBS sialylated capsular polysaccharide interactions with Siglec-9. Thus, GBS can impair neutrophil defense functions by coopting a host inhibitory receptor via sialoglycan molecular mimicry, a novel mechanism of bacterial immune evasion.